Labor stress and organizational climate in collaborators of hospital “Solidaridad” in Chiclayo - Díaz Dávila, Fiorela (2019)
The present work of investigation titled labor stress and organizational climate in the collaborators of the Hospital of the Solidarity Chiclayo, 2018, had like general objective To determine the level of relation that exists between stress and organizational climate in collaborators, with a non experimental experimental design, cross-section of correlational type, taking as a sample a total of 30 technicians to whom a data collection instrument was applied, this being the Likert scale, which was validated according to expert judgment with a reliability level of 0.889. It was verified that the variables of work stress and organizational climate are related in an inverse and significant way (- 0.653) and given that p- value (0.000) <α (0.05), then h0 is rejected. In other words, the higher the organizational climate, the lower the level of work stress shown by the employees of the Hospital de la Solidaridad 2018.